ANALISIS RASIO UTANG ATAS MODAL DAN UKURAN PERUSAHAAN TERHADAP PENGEMBALIAN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Prayudi, Ahmad; Ilhammi, Nur (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2015)
Manufactury industry is the industry which produce unready-made goods tobe ready made goods. Manufactury industry has role in economy of the country. But the growth of economy fluctuation can not be avoided which causes influence on the companyâs stability that can be seen from the financial statement.This research has the direction to analyse debt to equity ratio and firm size to the stock return in manufacture company which is listed in Indonesia Stock Exchange. Data is taken from the publication financial statement which is gotten from www.idx.co.id for the periode 2010-2013. The population in this research is all the manufacture companies from sub sector of consumtion goods which are 36 companies and the samples with purposive sampling methode are 13 companies. The Analysis of data used is statistic descriptif analysis and multiple linear regression analysis to get the description spreadly about the correlation among variabels.The result of this research shows that debt to equity ratio influential positif and not significant to stock return. Meanwhile, firm size influential positif and significant to stock return.